Pengelolaan Manajemen Keuangan dalam Industri Kecil Menengah di Komunitas Tangsel Berkibar - Vivi Iswanti Nursyirwan; Eric Agustinus; Nani Mulyani (S1 Accounting Program, Universitas Pamulang, 2020)
AbstractOne of the components in Tridharma Colleges is implementing community service activities. Each lecturer has an obligation to perform devotion to the community who aims to share the knowledge that has to support the progress of society. The implementation of community dedication in this activity is the management of financial management in the small and medium industries in the Tangsel Berkibar community. Small and medium industries are one of the businesses that produce various types of products on the small and medium scale in accordance with the regulation of the Minister of Industry No. 64/M-IND/7/2016.Small and medium-sized enterprises have a strategic role in national economic development. These dedication activities are also in line with government programs that drive the advancement of small and medium enterprises. The goal of this activity is the members of the Tangsel Berkibar community. This Program is implemented for 3 days (26-28 April 2019). The method is to provide training on financial management for the small and medium industries. The results showed that the participants were enthusiastic about training to run the financial arrangements in his business. For subsequent devotion, activities are expected to provide ongoing training to improve the ability of small and medium industry actors in implementing financial management.